Synthesis and characterization of Ag ION doped ZnO nanostructures deposited on gold seeded substrate / Nurul Afaah Abdullah - Abdullah, Nurul Afaah (2017)
High quality of (002) c-axis preferential growth of ZnO is vital as the properties of devices is enhanced. In this work, ZnO nanorods were grown on ZnO seed layer. The preparation towards the optimization of ZnO nanorods was studied. This work consists of two major parts, which are the preparation of ZnO seed layer and the preparation of ZnO nanorods on the ZnO seed layer. Firstly, ZnO seed layer was prepared by vapor method; mist-atomization at ambient --condition. To increase the adhesion of ZnO seed layer towards glass substrate, gold layer was coated onto the glass substrate by sputtering method. FESEM and UV-vis results gave evidence that 6 nm thickness of gold layer on glass substrate provided the best nucleation site for the growth of ZnO seed layer with high uniformity and enhanced absorbance properties. The effect of substrate temperature to the growth of ZnO seed layer was studied.